The Influence of Singing Method on Expression of Children's Emotion at Kindergarten of Jabal Rahmah Padang - Nadia Resika; Indra Yeni (SELING: Jurnal Program Studi PGRA, 2019)
The method that can develop children's emotional expression is to use the method of singing, based on the background of the problem that researchers found, this study wants to find out the extent of the effect of the singing method on children's emotional expression. The research approach used quasi-experiment with the subject: group B1 consisted of10 children in which 6 boys and 4 girls, and group B2 consisted of 10 children in which 7 boys and 3 girls. The data collection techniques used were action tests, with tools collection data using statement sheets, then managed using a data difference test (t-test). The results showed the experimental class with the singing method got an average value of 88.75 higher than those in the control class 78.12 using the role-playing method. Visible t count > t table is 2,41590> 2.10092. It can be concluded that the method of singing affects the emotional expression of children in kindergarten Jabal Rahmah Padang in 2018/2019 school year